2006
DOI: 10.1029/2006gb002727
|View full text |Cite
|
Sign up to set email alerts
|

Possible overestimation of shallow‐depth calcium carbonate dissolution in the ocean

Abstract: [1] We argue that diagnostics of excess dissolved calcium carbonate (TA*) above the saturation horizon cannot be unambiguously interpreted in terms of local in situ dissolution. We examine a three-dimensional numerical model of global ocean circulation and biogeochemistry with explicit representation of the formation and dissolution of calcium carbonate. In particular, dissolution is only allowed to occur below the saturation horizon. The model qualitatively captures the observed basin-and global-scale pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
63
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 56 publications
4
63
0
Order By: Relevance
“…There are in fact several tracer-based studies reporting CaCO 3 dissolution above the saturation horizon of bulk seawater (Barrett et al, 2014;Feely et al, 2002Feely et al, , 2004Sabine et al, 2002b;Chung et al, 2003). In a modelling study, Friis et al (2006), nevertheless, demonstrated that the method which is often employed to derive these upper ocean dissolution rates (Berelson et al, 2007, see Discussion section on TA * CFC age method), might not be applicable, because this method neglects physical transport and mixing of alkalinity. It is therefore still debated where and how fast settling CaCO 3 particles are dissolved in the water column.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are in fact several tracer-based studies reporting CaCO 3 dissolution above the saturation horizon of bulk seawater (Barrett et al, 2014;Feely et al, 2002Feely et al, , 2004Sabine et al, 2002b;Chung et al, 2003). In a modelling study, Friis et al (2006), nevertheless, demonstrated that the method which is often employed to derive these upper ocean dissolution rates (Berelson et al, 2007, see Discussion section on TA * CFC age method), might not be applicable, because this method neglects physical transport and mixing of alkalinity. It is therefore still debated where and how fast settling CaCO 3 particles are dissolved in the water column.…”
Section: Introductionmentioning
confidence: 99%
“…Equation (ueq kg −1 ) Mean RMSE from Global (mol m −3 ) B3D (mol m −3 ) Gruber et al (1996) Gruber et al (1996) is the original, global regression based on two explanatory variables (based on their 1996 database). Feely et al (2002) and Friis et al (2006) are both taken from Sabine et al (2002b), also including temperature as an additional explanatory variable and fitted to a Pacific subset. Global B3D 2V is a global regression with two explanatory variables (based on WOA09 Locarnini et al, 2010;Antonov et al, 2010;Garcia et al, 2010a, b) on the Bern3D grid (32 × 40 × 41 grid cells).…”
Section: Introductionmentioning
confidence: 99%
“…Where A T data was not available (1991,1994,2009) To investigate the vertical distribution of A T in the water column without the effect of salinity, it was normalised to a salinity of 35 as described by Friis et al (2003) and O 2 are estimated it increases to ±5µmol kg -1 . Since ∆C T-abio is independent of the effects of the biological pump, it can therefore be assumed that any changes in ∆C Tabio within a water mass are due to increasing levels of anthropogenic CO 2 .…”
Section: Dissolved Inorganic Carbon (C T ) and Total Alkalinitymentioning
confidence: 99%
“…A number of studies have found that dissolution of CaCO 3 can occur above the saturation horizon (e.g. Chen, 2002;Feely et al, 2004;Milliman et al, 1999); however it may not be a significant process in the North Atlantic (Friis et al, 2006a;Friis et al, 2006b). Aragonite is more soluble than calcite and the aragonite saturation horizon (ASH) occurs at shallower depths, ~3500m deep in the North Atlantic .…”
Section: Introductionmentioning
confidence: 99%
“…Chung et al [2003] and Feely et al [2002] have suggested that much of the excess alkalinity in the upper waters could be due to the dissolution of particles within the upper water column. Friis et al [2006] suggested that the excess alkalinity in the upper water column could be derived from dissolution of CaCO3 from the sediment. The role of river-derived alkalinity on these estimates is also uncertain, but potentially important [e.g., Lee et al, 2006].…”
mentioning
confidence: 99%